2021
DOI: 10.1155/2021/6678755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Anthropometric Indicators for Screening for Nonalcoholic Fatty Liver Disease in Elderly Individuals

Abstract: Objective. To explore the anthropometric indicators suitable for screening for nonalcoholic fatty liver disease (NAFLD) in the elderly population. Methods. This cross-sectional study screened subjects over 65 years, who had undergone a physical examination in 2019. Their height, weight, waist circumference, and fasting blood glucose and triglyceride levels were measured. Body mass index (BMI), waist circumstance (WC), waist-to-height ratio (WHtR), relative fat mass (RFM), ponderal index (PI), conicity index (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
3
12
2
1
Order By: Relevance
“…Their findings contradicted the research of Lin et al, who found that the best indicator of NAFLD screening was AVI, not HSI [22]. Additionally, in a recent study, Zhang et al evaluated the predictive value of relative fat mass, WC, ABSI, WHtR, COI, ponderal index, BMI, and LAP for NAFLD in the elderly; their study showed that LAP was the best marker of these parameters for predicting NAFLD [23]. This study confirms the conclusion of Zhang et al, and in further analysis, it was found that LAP was superior to the TyG index, WHtR, ABSI, COI, BMI, TG/HDL-C ratio, WC, VAI, TG, and BRI in both males and females.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Their findings contradicted the research of Lin et al, who found that the best indicator of NAFLD screening was AVI, not HSI [22]. Additionally, in a recent study, Zhang et al evaluated the predictive value of relative fat mass, WC, ABSI, WHtR, COI, ponderal index, BMI, and LAP for NAFLD in the elderly; their study showed that LAP was the best marker of these parameters for predicting NAFLD [23]. This study confirms the conclusion of Zhang et al, and in further analysis, it was found that LAP was superior to the TyG index, WHtR, ABSI, COI, BMI, TG/HDL-C ratio, WC, VAI, TG, and BRI in both males and females.…”
Section: Discussionmentioning
confidence: 82%
“…At present, there are very few comparative studies on the prediction of NAFLD by obesity and lipid-related indices. The conclusions of several existing studies are controversial, and do not include TyG indexrelated parameters [21][22][23]. According to some recent studies, TyG index-related parameters are promising new indicators for predicting NAFLD [14,24].…”
Section: Introductionmentioning
confidence: 99%
“…The values of the 11 obesity indices analyzed resulted higher in the NAFLD than the NO-NAFLD group as con rmed in other studies. A previous study showed good discriminatory ability of BMI, WHtR, CI, LAP, and ABSI were measured in the diagnosis of NAFLD 9 , and another study reported that TyG level is an independent risk factor of NAFLD, and TyG index plays a partial mediating role in the relationship between WHtR and NAFLD 24 . In patients with type 2 diabetes, the non-invasive HIS score is considered as an easy, convenient and inexpensive screening for fatty liver 25 .…”
Section: Discussionmentioning
confidence: 93%
“…For example, the visceral adiposity index (VAI) and the triglycerides and glucose (TyG) index have been applied in a NAFLD-related prediction models 6 . Besides, body roundness index (BRI), a body shape index (ABSI), conicity index (CI), Clínica Universidad de Navarra-body adiposity estimator (CUN-BAE), triponderal mass index (TMI) have proved to be effective predictors of MetS and NAFLD [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Kobo i wsp. [31] stwierdzili, że ten nowy wskaźnik zapewnia wysoką przewidywalność dyslipidemii i zespołu metabolicznego, a także niealkoholowej stłuszczeniowej choroby wątroby (NAFLD) [32].…”
Section: Wskaźnik Relatywnej (Względnej) Tkanki Tłuszczowej -Rfm (Relative Fat Mass)unclassified